Impactful Kol Marketing For B2C In Social Commerce: Create Powerful, Viral And Long-Lasting Campaign In Various Medium And Industries - Ade Nurhasanah; Dede Djuniardi (International Journal Labs, 2024)
In today's digital era, marketing through Key Opinion Leaders (KOLs) has become a very effective strategy in reaching a wider audience and building consumer trust. KOLs, or often known as influencers, have the unique ability to influence the purchasing decisions of their followers through the content they share on various social media platforms. This article aims to achieve significant success in KOL marketing, especially in B2C (Business-to-Consumer) in the realm of social commerce, a well-planned strategy and proper execution are required. This study uses a qualitative approach by means of an in-depth literature review related to KOL Marketing for B2C in social commerce. The results of research on Impactful KOL Marketing for B2C in Social Commerce which includes the creation of strong, viral, and sustainable campaigns across various mediums and industries and efforts to measure their impact comprehensively may not be found in many specifics. In the use of Key Opinion Leaders (KOLs) for B2C marketing strategies in social commerce, it is evident that this approach has great potential to increase brand exposure, consumer engagement, and ultimately, sales.